EDUKASI HUKUM PENDAFTARAN DAN PERLINDUNGAN MEREK DAGANG, PATEN, DESAIN INDUSTRI BAGI KARYAWAN DIVISI HUKUM PT. GLOBAL JET E-COMMERCE - Gede Aditya Pratama; Adi Nur Rohman (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Intellectual Property is a right that arises from the results of thinking that produces a product or process that isuseful for humans. In essence, intellectual property is the right to enjoy economically the results of an intellectual creativity. IPR consists of various rights including copyrights, trademarks, patents, industrial designs, and trade secrets. Legal counseling on the importance of IPR was delivered to employees of the legal division of PT. GlobalJet E-Commerce. This counseling aims to increase the legal knowledge of legal division employees regarding the process of registering and protecting trademarks, industrial designs and so on. After the legal counseling wascarried out, participants understood that trademarks and industrial designs are intellectual property that must bemaintained and protected. In addition, participants also understand that the process of registering intellectual property is carried out by first carrying out an inspection of the registered mark to minimize rejection of trademark registration.